The Effect of Research-based Digital Module towards Students' Science Literacy Ability in Static Fluid Materials - Tia Rachma Fajaryanti; Erina Hertanti (Berkala Ilmiah Pendidikan Fisika, 2022)
The main problem of this study is the implementation of physics learning activities that do not involve the scientific process that can train students' science literacy ability, especially in the competence aspects. As a result, the development of students' science literacy ability is not maximal. A solution given in this study is a research-based digital module as teaching material. This study was conducted at SMA Dharma Karya UT with a quasi-experimental method and nonequivalent control group design. The study used purposive sampling to decide the study's sample with the following classification XI IPA 2 as the experimental class with 25 samples and XI IPA 1 as the controlled class with 25 samples. The instruments of the study were test and non-test. The science literacy test contained ten questions, and the non-test was a questionnaire. In addition, based on a statistical calculation of the post-test by using a nonparametric test, Mann-Whitney showed that a significant score 2-tailed (0.011) < significant level (α=0.05). It showed a research-based digital module's effect on students' science literacy ability. Meanwhile, the result of N-Gain showed the enhancement of students' science literacy ability; this can be seen from the superior N-Gain value in the experimental class. Moreover, the questionnaire also showed that using research-based digital modules for students' science literacy ability was good (73%).